MEDIASI SEBAGAI UPAYA PENYELESAIAN PERCERAIAN BERDASARKAN PERMA NOMOR 1 TAHUN 2016 DI PENGADILAN AGAMA MAKASSAR - Andriyana, Rina (Al-Hikmah, 2019)
Abstract The research was conducted and aimed at: 1) To find out the application of mediation as a divorce settlement based on Perma Number 1 of 2016 in the Makassar Religious Court; 2) To find out and analyze what factors are obstacles Mediator in conducting divorce mediation in the Makassar Religious Court ..This type of research is empirical legal research, namely legal research that examines the implementation or implementation of positive legal provisions (legislation) factually on any particular legal event that occurs in society. The legal material used consists of primary legal data and secondary legal data. Techniques for collecting legal data are collected through literature studies and field studies. Then the technique for analyzing with qualitative analysis techniques by sorting and selecting, classifying, and connecting the realities that occur in the field with the problems studied, so as to provide a clear picture of what happened in the field so that it comes to a conclusion.The results showed that: 1) The application of mediation as an attempt to resolve divorce based on Perma Number 1 of 2016 had gone even though the success rate of the mediation process was very lacking, data from the mediation report from 2018 to 2019 there were only 23 divorce cases that were successfully reconciled during the total mediation process the overall case was 3498 cases; 2) Factors that inhibit mediators in the implementation of mediai in the Makassar Religious Court, in terms of mediators that are still insufficient in number, the number of cases handled is very large, the backgrounds of editorial judges are generally not certified mediators from the Supreme Court. In terms of the parties who do not want peace and from the point of view of Advocates who represent their clients in the mediation process so that the mediator does not interact directly with those who want to divorce.